Pengaruh Kepercayaan, Gaya Kepemimpinan Transaksional, Dan Kompetensi Sumber Daya Manusia Terhadap Kinerja Karyawan (Studi Pada Koperasi Se-Kecamatan Sape Kabupaten Bima Nusa Tenggara Barat) - Nurwasilah Nurwasilah; Budi Wahono; Mohamad Bastomi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to analyze the effect of trust, transactional leadership style, and human resource competence on the performance of cooperative employees in Sape District, Bima Regency. This research method uses quantitative research methods with explanatory research types. The primary data source was obtained from questionnaire data which was measured using a Likert scale. The population used is all cooperative employees in Sape District, Bima Regency, where the number of cooperative in Sape District is 21 units. The research sample was all cooperative employees whose number was determined using the Slovin formula so that a total of 76 people were obtained. The results of this study indicate that 1) Trust, transactional leadership style, and human resource competence simultaneously affect the performance of cooperative employees in Sape District, Bima Regency. 2) Trust does not have a significant negative effect on the performance of cooperative employees in Sape District, Bima Regency. 3) Transactional leadership style has a positive and significant effect on the performance of cooperative employees in Sape District, Bima Regency. 4) Competence of human resources has a positive and significant effect on the performance of cooperative employees in Sape District, Bima Regency. Keywords : Trust, Transactional Leadership Style, Human Resource Competence, Employee Performance.